Poly(3-hydroxybutyrate) influences biofilm formation and motility in the novel Antarctic species Pseudomonas extremaustralis under cold conditions - Tribelli, Paula Maria; López, Nancy Irene (Extremophiles)
Polyhydroxyalkanoates (PHAs) are highly reduced bacterial storage compounds that increase fitness in changing environments. It has previously shown that polyhydroxybutyrate (PHB) accumulation is essential during the growth under cold conditions. In this work, the relationship between PHB accumulation and biofilm development at low temperature was investigated. P. extremaustralis, an Antarctic strain able to accumulate PHB, and its phaC mutant, impaired in the synthesis of this polymer, were used to analyze microaerobic growth, biofilm development, EPS content and motility. PHB accumulation increased motility and survival of planktonic cells in the biofilms developed by P. extremaustralis under cold conditions. Microaerobic conditions rescued the cold growth defect of the mutant strain. The PHB accumulation capability could constitute an adaptative advantage for the colonization of new ecological niches in stressful environments. © 2011 Springer. Fil: Tribelli, Paula Maria. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina Fil: López, Nancy Irene. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica; Argentina